Mengintegrasikan Analisis SWOT dan Business Model Canvas: Pendekatan Strategis untuk Kedai Kopi di Indonesia - Rendy Sumara (Komunitas Dosen Indonesia, 2024)
The coffee shop industry in Indonesia has experienced significant growth due to changing consumer preferences towards urban lifestyles and coffee consumption as a daily habit. Coffee shops have evolved into centres for socializing and conducting business, contributing to Indonesia's creative economy by promoting local employment, creativity, and innovation. This research aims to investigate the strategic combination of SWOT Analysis and the Business Model Canvas to improve the competitiveness and sustainability of coffee shops, focusing specifically on Kedai Kopi Semangat in Bekasi. The study utilizes a qualitative approach, incorporating in-depth interviews, participant observation, and online review analysis. Data were collected through semi-structured interviews with owners, managers, baristas, and customers, as well as participant observation to capture daily interactions and operational practices. Additionally, online reviews were analyzed to gain insights into customer perceptions and satisfaction. Through a case study design, a comprehensive exploration of phenomena in the unique context of Kedai Kopi Semangat is conducted, offering valuable contextual insights. The findings reveal several strengths of Kedai Kopi Semangat, such as an iconic rooftop area, strategic location, and strong brand visibility. However, the coffee shop also faces notable weaknesses, including limited parking access and high costs of goods sold (COGS). Opportunities identified include the growing trend of specialty coffee consumption and the increasing popularity of local coffee shops. Conversely, threats consist of frequent new coffee shop openings and economic fluctuations that could affect consumer spending. The study concludes that integrating SWOT Analysis and the Business Model Canvas provides a robust framework for strategic planning and business sustainability. This integrated approach helps coffee shop owners optimize their strengths, address weaknesses, seize opportunities, and mitigate threats. The strategic insights gained from this research can guide coffee shop owners in navigating the complexities of the market and achieving long-term success. By addressing the specific needs and challenges of coffee shops in Indonesia, this study contributes to the overall development and sustainability of the industry, offering practical implications for business owners and managers. Specifically, the research suggests targeted strategies such as enhancing customer experience, optimizing operational efficiency, and developing innovative marketing approaches to ensure sustained competitive advantage.